Prevalence and characterization of the mechanisms of macrolide, lincosamide and streptogramin resistance in viridans group streptococci. - Ioannidou, Sofia; Papaparaskevas, Joseph; Tassios, Panayotis T; Foustoukou, Maria; Legakis, Nicholas J; Vatopoulos, Alkiviadis C (Int J Antimicrob Agents, 2003)
The presence of erm genes conferring constitutive and inducible resistance, as well as that of the mefA gene conferring only constitutive resistance, was investigated using PCR in 70 erythromycin resistant (MIC>or=1 mg/l) strains of viridans group streptococci (VGS) (18 Streptococcus mitis biotype 1, 16 S. mitis biotype 2, 15 S. oralis, 12 S. salivarius and nine S. sanguis) isolated from the oropharynx of healthy Greek children. All of the 56 isolates belonging to resistance phenotype M harbored the mefA gene. All of the 14 isolates constitutively resistant to macrolides and lincosamides (phenotype CR) harbored the ermB gene. Co-presence of both genes was not observed, whereas class A erm gene (previously known as ermTR) was not detected. Our results are consistent with a possible role of VGS as a reservoir of resistance genes now prevalent in pathogenic species of streptococci.
Keywords: Anti-Bacterial Agents; Base Sequence; Child; DNA, Bacterial; Drug Resistance, Bacterial; Genes, Bacterial; Humans; In Vitro Techniques; Lincosamides; Macrolides; Oropharynx; Phenotype; Streptogramins; Viridans Streptococci